2016
DOI: 10.3174/ajnr.a4832
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stiffness of 4 Common Intracranial Tumors Measured Using MR Elastography: Comparison with Intraoperative Consistency Grading

Abstract: BACKGROUND AND PURPOSE:The stiffness of intracranial tumors affects the outcome of tumor removal. We evaluated the stiffness of 4 common intracranial tumors by using MR elastography and tested whether MR elastography had the potential to discriminate firm tumors preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…In these studies, low grade gliomas were not included and no statistical analysis was reported for the relationship between tumor mechanical properties and tumor grade or IDH1 mutation status. A recent study demonstrated good correlation between glioma stiffness measurements and surgical assessment 19 . The results of this study are consistent with the quantitative stiffness values of gliomas reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In these studies, low grade gliomas were not included and no statistical analysis was reported for the relationship between tumor mechanical properties and tumor grade or IDH1 mutation status. A recent study demonstrated good correlation between glioma stiffness measurements and surgical assessment 19 . The results of this study are consistent with the quantitative stiffness values of gliomas reported in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have demonstrated the feasibility of using MRE to evaluate the viscoelastic properties of brain tumors including gliomas, where brain tumors were mainly softer than normal brain and benign variants, however some tumors are stiffer than normal brain 17 and GBMs were the softest brain tumors when compared to meningiomas, vestibular schwannomas, and metastases 18, 19 . Additional work demonstrated that viscoelastic properties of GBMs were dependent on composition (e.g., necrosis or cystic cavities) and that the mechanical properties were heterogeneous with both stiff and soft regions 17, 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time harmonic steady state shear wave pattern is then used as input to a linear inversion of the wave equation to estimate biomechanical properties, which are then displayed in elastographic maps or elastograms . Several studies have shown that stiffness, as measured with MRE, is in good agreement with tumor consistency assessed by a neurosurgeon intraoperatively . In addition, different tumor types vary in their biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Several studies have shown that stiffness, as measured with MRE, is in good agreement with tumor consistency assessed by a neurosurgeon intraoperatively. 6,[13][14][15] In addition, different tumor types vary in their biomechanical properties. A general observation is that intracranial malignancies are softer than benign tumors or healthy brain parenchyma.…”
mentioning
confidence: 99%